The Feedback 5: Principles for Providing Effective Written Feedback on Students' Work (Journal on Excellence in College Teaching, 2024)
Assessing student work generally involves offering comments that identify mistakes and evaluate the achievement of learning goals. Instructor-written feedback, though crucial to encouraging learning, can be a controversial practice. Instructors often expect that students will undervalue or ignore their feedback, caring only about grades. Students often report that they ignore feedback because they cannot understand or use it. Feedback is ineffective when students are unable to apply it to improve their performance. This article reviews literature from several disciplines to identify strategies and principles that can guide instructors in providing effective written feedback that will encourage and support student learning.